1998
DOI: 10.1083/jcb.142.5.1257
|View full text |Cite
|
Sign up to set email alerts
|

Development of Approaches to Improve Cell Survival in Myoblast Transfer Therapy

Abstract: Myoblast transplantation has been extensively studied as a gene complementation approach for genetic diseases such as Duchenne Muscular Dystrophy. This approach has been found capable of delivering dystrophin, the product missing in Duchenne Muscular Dystrophy muscle, and leading to an increase of strength in the dystrophic muscle. This approach, however, has been hindered by numerous limitations, including immunological problems, and low spread and poor survival of the injected myoblasts. We have investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
416
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 423 publications
(436 citation statements)
references
References 72 publications
13
416
1
6
Order By: Relevance
“…Although MSCs have been shown to participate in myocardial repair, their homing to infarcted area and their survival post transplantation are limited [16]. The cell viability may ultimately determine the final outcome of cardiac repair [17]. CXCR4 is receptor for SDF-1α and is very important in the stem cell migration, homing, and survival [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although MSCs have been shown to participate in myocardial repair, their homing to infarcted area and their survival post transplantation are limited [16]. The cell viability may ultimately determine the final outcome of cardiac repair [17]. CXCR4 is receptor for SDF-1α and is very important in the stem cell migration, homing, and survival [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that early preplates (pp1-2) contain a majority of fibroblasts (5-15% desmin-positive) and the late preplates (pp5-6) are enriched with desmin-positive cells (>80%). [20][21][22]41 The cells used in this experiment were taken from the late preplate (pp6) and were shown to express myogenic and stem cell markers. 9 The proliferation medium used to grow the cells was Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 10% horse serum (HS) and 1% penicillin/streptomycin.…”
Section: Purification Of Primary Muscle-derived Cellsmentioning
confidence: 99%
“…[7][8][9][10] However, the transplantation of donor muscle cells into host muscle has been hindered by various limitations, such as immune rejection that consequently leads to poor spreading and survival of injected cells. [11][12][13][14][15][16][17][18][19][20] The success of cell transplantation may be dramatically improved by using a specific population of cells that has the capacity to overcome these hurdles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the imaging modality to be used, stem cells can be labeled with radionuclides for SPECT or PET [32][33][34][35] and SPIO for MRI (Fig. 1) [36,37]. Direct cell labeling is fairly simple and does not involve genetic modification of the cell.…”
Section: Direct Labelingmentioning
confidence: 99%